UJI BIOFUEL HASIL PERENGKAHAN METIL ESTER DARI LIMBAH CAIR PABRIK MINYAK KELAPA SAWIT DENGAN KATALIS MoNi/HZ - Dian Kartika Sari; Agus Sundaryono; Dewi Handayani (ALOTROP, 2017)
[CONVERSION OF LIQUID WASTE OIL PALM OIL FACTORY BECOME BIOFUEL WITH MONi / HZ CATALYST] This study aims to produce biofuel from liquid waste oil PMKS with worditik cracking using catalystMoNi / HZ. This study involves the preparation of a catalyst performed by means of a separate impregnation, this impregnation lasting for 12 hours. The next stage of sample preparation includes heating, filtering, degumming, bleaching and ALB determination, followed by the production of methyl esters through esterification and transesterification processes. Then the obtained methyl ester was cracked using a catalyst for 2 hours at 380 °C and followed by distillation of the product for 2 hours at 380 °C, followed by distillation step at 380 °C to obtain methyl ester. The physical characteristics of biofuel resulting from the catalytic cracking reaction of the methyl ester using the MoNi / HZ catalyst of the PMKS wastewater include the acid number 1.92 mg KOH / g, density 0.803 g/cm3, kinematic viscosity 1,113 cSt, a pour poin of 0oC and fog poin at 1,43 oC. Biofuel resulting from catalytic cracking using this MoNi / HZ catalyst of very high biofuel acid numbers can be used in areas that have a cold climate. the biofuel viscosity of the experimental results has not matched the viscosity of gasoline or kerosene, so it can not be used as fuel equivalent to gasoline and kerosene with the composition of 100% biofuel density from biofuel is still slightly above gasoline and kerosene